Effect of pH on Homogeneous Photodegradation of Eosin Y Dye - Roy, Subrata Chandra; Mahmood, Abu Jafar (Journal of Nepal Chemical Society, 2021)
Eosin Y (EY), an anionic dye, also known as Eosin Yellow or Bromoeosin, or Acid red 27 is an industrial dye. The residual dye, discharged as one of the components of the untreated effluent, into the adjacent surface and causes water pollution. Photodegradation of EY was investigated at 29 oC in homogeneous aqueous media using UVA light (≈400 – 320 nm) in acetate buffer solution as a function of pH (3.08-7.08). At higher pH, there was no effect of this light on the dye in the solution. Results show that the initial rate of photocolorization increased with decreasing the pH of the dye solution.